2021
DOI: 10.3390/biom11081145
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and Characteristic Analysis of RING-DUF1117 E3 Ubiquitin Ligase Genes in Gossypium Discerning the Role of GhRDUF4D in Verticillium dahliae Resistance

Abstract: Verticillium wilt, primarily induced by the soil-borne fungus Verticillium dahliae, is a serious threat to cotton fiber production. There are a large number of really interesting new gene (RING) domain-containing E3 ubiquitin ligases in Arabidopsis, of which three (At2g39720 (AtRHC2A), At3g46620 (AtRDUF1), and At5g59550 (AtRDUF2)) have a domain of unknown function (DUF) 1117 domain in their C-terminal regions. This study aimed to detect and characterize the RDUF members in cotton, to gain an insight into their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Several DUF family genes related to salt stress response have been reported. Overexpression of soybean GmCBSDUF3 , encoding DUF21, can enhance the tolerance of Arabidopsis thaliana to both drought and salt stress [ 42 ]. Overexpression of AhDGR2 (encoding a protein containing a DUF642 domain) in ‘Nipponbare’ resulted in increased sensitivity to NaCl treatment [ 43 ], OsSIDP366 (a gene containing DUF1644) positively regulates the response of rice to drought and salt stress [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several DUF family genes related to salt stress response have been reported. Overexpression of soybean GmCBSDUF3 , encoding DUF21, can enhance the tolerance of Arabidopsis thaliana to both drought and salt stress [ 42 ]. Overexpression of AhDGR2 (encoding a protein containing a DUF642 domain) in ‘Nipponbare’ resulted in increased sensitivity to NaCl treatment [ 43 ], OsSIDP366 (a gene containing DUF1644) positively regulates the response of rice to drought and salt stress [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…qGL3.5 encodes an IBR-RING zinc-finger protein with one RING and two IBR domains. Proteins containing zinc finger domains and RING-finger domains were found to play important roles in eukaryotic cells by regulating different signal transduction pathways and biological processes, such as plant growth development and resistance ( Yilmaza and Mittlera, 2008 ; Sun et al, 2019 ; Zhao et al, 2021 ). Duan et al (2020) reported a Cys2/His 2 zinc finger protein, ZFP207, that acts as a transcriptional repressor of OsGA20ox2 and negatively regulates plant height and GL in rice.…”
Section: Discussionmentioning
confidence: 99%
“…As in tomato, cotton plants are able to induce expression of NBS-LRR defence genes by suppressing the miR482-mediated gene silencing pathway upon fungal pathogen attack [ 80 ]. Particularly, miR482c might participate in cotton growth and abiotic stresses including drought stress response as a potential regulator [ 81 ]. As sequence variation induced target and mechanism variation, the function of members in miR482 family differ possibly from each other [ 78 , 82 ].…”
Section: Discussionmentioning
confidence: 99%